Exam timetable for unimas-enhancement of sistem jadual waktu UNIMAS - Voon, Tze Min (Universiti Malaysia Sarawak, UNIMAS, 2005)
For the current exam timetabling system in Unimas, some problems and weakness arise. The procedure of booking the venue for final exam is complicated and is done manually. In addition, current Sistem Jadual Waktu Unimas has some weakness. A proper searching method and algorithm is not applied for that system. Hence, the Unimas Examination Timetabling System is developed. It is a computerized system to help the Academic department to simplify the process of arranging the examination timetable. The timetable will be generated through the adoption of the genetic algorithm. This is a web-based system which is developed using Object Oriented Methodology, PHP and MySQL. The main feature of this system is the automation generation of the examination timetable from the course information. Hopefully, this system will help to decrease and solve the problem such like clashing among timeslots, clashing among venue and clashing among lecturer’s timetable.